PENANAMAN NILAI DEMOKRASI DI KAWASAN MULTIKULTURAL: Menilik Sekolah Khong Kauw Hwee Semarang - Aris Nurlailiyah (Mukaddimah: Jurnal Studi Islam, 2022)
Pecinan (Chinatown) is a form of ancient civilization that still persists today. In the context of Java, the population of Pecinanconsists of various ethnic groups ( Javanese, Chinese), who believe in various faiths (Islam, Confucianism, Catholicism, Protestantism, Hinduism, Buddhism). In the midst of the Pecinan multicultural community in Semarang, Central Java, stands Khong Kauw Hwee School, an educational institution that emphasizes character building of the students. One of its strategies is by teaching democratic values. The school instills public virtues to the students in daily practices i.e installing boards with wisdom words and setting up honest-stalls, besides conventional teachings in the classrooms. Khong Kauw Hwee is not limited by exclusive fences, yet transforming into an open school that expand its spaces to establish relationships and participation with surrounding communities. The school is open for any religion or faith and free of charge for those in need. By doing so, democratic values-teaching of the school is in an interrelated situation with the socio-cultural life of the surrounding communities. Keyword: Democratic value, multicultural city, Khong KauwHwee School